2016
DOI: 10.1016/j.jclepro.2015.12.074
|View full text |Cite
|
Sign up to set email alerts
|

Can the environmental impact of pig systems be reduced by utilising co-products as feed?

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints -eprint.ncl.ac.uk Mackenzie SG, Leinonen I, Ferguson N, Kyriazakis I. Can the environmental impact of pig systems be reduced by utilising coproducts as feed?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 35 publications
2
53
1
1
Order By: Relevance
“…The reduction of dietary CP content led to a slight increase in AP and EP impacts per kg of feed (Table 1). This result was also observed in previous studies (Mosnier et al, 2011;Garcia-Launay et al, 2014;Mackenzie et al, 2016;Monteiro et al, 2016Monteiro et al, , 2017b.…”
Section: Potential Of Acidification and Eutrophicationsupporting
confidence: 91%
See 1 more Smart Citation
“…The reduction of dietary CP content led to a slight increase in AP and EP impacts per kg of feed (Table 1). This result was also observed in previous studies (Mosnier et al, 2011;Garcia-Launay et al, 2014;Mackenzie et al, 2016;Monteiro et al, 2016Monteiro et al, , 2017b.…”
Section: Potential Of Acidification and Eutrophicationsupporting
confidence: 91%
“…Nitrogen and phosphorus contribute to the eutrophication process and nitrogen contributes to the acidification process by ammonia emissions (Guinée et al, 2002). For this reason, most research evaluating the effect on dietary CP reduction for pigs reported a reduction on AP and EP with low CP diets (Ogino et al, 2013;Garcia-Launay et al, 2014;Mackenzie et al, 2016;Kebreab et al, 2016). In the above-mentioned researches, data were not evaluated statistically and the effect of between-animal variability was also not taken into account.…”
Section: Potential Of Acidification and Eutrophicationmentioning
confidence: 99%
“…Comparing diets based on meat meal, with dietary CP of 147g kg -1 , and diets based on bakery meal, with 132g CP kg -1 , AP and EP impacts were reduced by about 6 and 7%, respectively, for each percentage unit of dietary CP reduction (MACKENZIE et al, 2016). According to KEBREAB et al (2016), the addition of industrial AA and phytase to pig diets also reduced EP and AP in all the regions studied.…”
Section: Nutrition and Acidification And Eutrophication Potential Of mentioning
confidence: 90%
“…The study carried out by MACKENZIE et al (2016) showed that using meat meal in pig diets increased the dietary CP compared to a control feed based on maize and soybean meal (147 vs. 133g CP kg -1 , respectively). However, the GWP of one kg of pig carcass was 2% lower when pigs were fed diets based on meat meal, in a Canadian pig farming system.…”
Section: Nutrition and Global Warming Potentialmentioning
confidence: 99%
“…Incorporation of SBP (10%) into a poultry diet based on corn, sunflower meal, barley, and wheat increases its water-holding capacity (+30%) and its swelling capacity (+15%) . Its use in goose diets has no detrimental effects on geese reared for meat production (Arslan, 2003(Arslan, , 2005 and could help mitigate the environmental consequences of both the animal production system (Mackenzie et al, 2016) and the biofuel industry (Popp et al, 2016). Additionally, Arroyo et al (2015) showed that SBP incorporation (10%) in a complete pelleted diet for geese reared for foie gras production tended to increase the crop volume of the birds (+8%).…”
Section: Introductionmentioning
confidence: 99%